Prevalence and Diagnosis of Sesame Allergy in Children with IgE-Mediated Food Allergy - Sokol, Kristin (Pediatr Allergy Immunol, 2019)
iii. Sesame allergy is estimated to affect 17% of children with IgE-mediated food allergy, and often co-occurs with peanut/tree nut sensitization and allergy. Sesame-specific IgE levels may have utility in the clinical management of these patients.